(untitled) (University of Khartoum Journal of Agricultural Sciences, 2021)
The present research was carried out at Guneid Sugar Cane Research Center during two successive seasons 2013/14 and 2014/15. The objective was to investigate the effect of four tillage systems (moldboard ploughing (T1), disc ploughing (T2), chisel ploughing (T3) and disc harrowing (T4)), three irrigation intervals (7, 10, and 14 days) and two planting methods (manual and mechanical) on sugar beet production. The parameters measured were machinery performance as effective field capacity (EFC), field efficiency (FE) and Fuel consumption (FC), some soil parameters (soil moisture content and bulk density), some crop parameters (root thickness (RT), crop root yield (RY), polarization or sugar content (Pol %), total sugar production (TSP) and cost of production. A spilt -split plot design with four replications was used in this study. The results showed that all machine performance parameters measured were significantly different and the highest EFC, FE and FC were recorded by the planter, ridger and chisel machines respectively. Tillage treatments and irrigation intervals interaction insignificantly affected soil moisture content and significantly (P≤0.01) affected soil bulk density. The highest values of RT (38.6 cm), RY (31.9 t/fed), Pol % (19.9 %) and TSP (4.9 t/fed) was recorded by (T3×M2×I1), (T2×M1×I2), (T4×M2×I3) and (T2×M1×I1) treatments respectively. The highest (4280 SDG/fed) and lowest (3290 SDG/fed) total cost of production was recorded by (T1×M1×I1) and (T4×M2×I4) treatments respectively. It can be concluded that generally disc ploughing with 10 days irrigation interval and manual planting can give higher crop root yield, higher TSP and lower cost of production at Guneid Sugar Cane Research Center